Assessment of nasal obstruction: Correlation between subjective and objective techniques (2013)
ABSTRACT: Background Nasal sensation of airflow describes the perception of the passage of air through the nose. Nasal obstruction can be assessed using subjective techniques (symptom scores and visual analogue scales [VAS]) and objective techniques (anterior rhinomanometry [RMN], acoustic rhinometry [AR], and peak nasal inspiratory flow [PNIF]). Few studies have evaluated the correlation between these techniques. Objective The primary objective of our study was to determine the degree of correlation between subjective and objective techniques to assess nasal obstruction. Materials and methods Nasal obstruction was assessed using a symptom score, VAS, RMN, AR (minimal cross-sectional area [MCSA] and volume), and PNIF in 184 volunteer physicians. Spearman's rho was recorded. Correlations were considered weak if r≤0.4, moderate if 0.4<r<0.8, and strong if r>0.8. Results Mean (SD) age was 37.1 (6.9) years (range, 25–56 years); 61% were women. We found a strong correlation (r>0.8; p=0.001) between the different parameters of RMN and a moderate correlation between symptom score and VAS (r=0.686; p=0.001) and between MCSA and RMN (resistance) (r=0.496; p=0.001) and PNIF (r=0.459; p=0.001). The correlations were weak or non-significant for the remaining comparisons. Conclusion Nasal obstruction can be assessed using subjective and objective approaches. The correlations between objective techniques were moderate to strong. In addition, between subjective techniques we reported a moderate correlation. Finally, the correlations between the subjective and objective techniques were weak and absent. These findings suggest that each of the techniques assesses different aspects of nasal obstruction, thus making them complementary.